QoS enabled networks : tools and foundations - Barreiros, Miguel, 1977-; Lundqvist, Peter, 1968- (Wiley, 2011)
With a foreword by Kannan Kothandaraman"This is the first book about QOS that I actually enjoyed reading precisely because the authors focused on real-life QoS and not in academic discussions about it."Per Nihlen, IP Network Manager, NORDUnetThe new authoritative, practical guide to delivering QOS guaranteesThis new benchmark in quality of service (QOS) study is written by two experts in the field who deal with QOS predicaments every day. The authors not only provide a lucid understanding of modern theory of QOS mechanisms in packet networks but how to apply them in practice. In addition, they